Stres Kerja Anggota Satlantas Polrestabes Semarang ditinjau dari Kepribadian Multikultural dan Hubungan Interpersonal dengan Rekan Kerja - Desy Caprisa Herlinda Anggraeni; Y. Bagus Wismanto; Daniel Purwoko Budi Susetyo (Faculty of Psychology, Universitas Semarang, 2023)
Abstract. The function of the Police that is vulnerable to work stress is the traffic function where the duties of the Traffic Unit include fostering traffic order, law enforcement and traffic order, registration and identification of drivers and motorized vehicles, so researchers want to examine to find out whether there is a relationship between multicultural personality and interpersonal relationships with colleagues with work stress members of the Semarang Traffic Police Traffic Unit. This study used a quantitative method with measuring tools such as the Work Stress Scale, the Multicultural Personality Scale, and the Interpersonal Relations Scale with Colleagues. Study The population of this study were members of the Semarang Police Traffic Unit. The sampling technique for this study used identifiable sampling. The data obtained were then analyzed with multiple linear regression. Based on the results of the analysis, it was found that there is a personality relationship with interpersonal relationships with co-workers and work stress for members of the Semarang Traffic Police Traffic Unit which produces a negative relationship in multicultural personality with work stress. with colleagues with work stress where the higher the interpersonal relationship with coworkers, the lower the work stress, the opposite will result. This means that there is a relationship between multicultural personality and interpersonal relationships with coworkers with work stress members of the Semarang Traffic Police Traffic Unit, and partially there is a very significant negative relationship between multicultural personality and work stress of members of the Semarang Polrestabes Traffic Unit, and interpersonal relationships with colleagues with work stress of members of the Semarang Traffic Police.Keywords: multicultural personality, interpersonal relationships, work stress Abstrak. Fungsi Kepolisian yang rentan terhadap stress kerja adalah fungsi lalu lintas dimana tugasn Satlantas meliputi pembinaan ketertiban lalu lintas, penegakan hukum dan ketertiban lalu lintas, regrestrasi dan identifikasi pengemudi dan kendaraan bermotor maka peneliti hendak meneliti untuk mengetahui apakah ada hubungan antara kepribadian multikultural dan hubungan interpersonal dengan rekan kerja dengan stres kerja anggota Satlantas Polrestabes Semarang. Penelitian ini menggunakan metode kuantitatif dengan alat ukur Skala Stres Kerja, Skala Kepribadian Multikultural, dan Skala Hubungan Interpersonal dengan Rekan Kerja. Studi Populasi penelitian ini adalah anggota Satlantas Polrestabes Semarang. Teknik pengambilan sampel penelitian ini menggunakan idencental sampling. Data yang diperoleh kemudian dianalisis dengan regresi linier berganda. Berdasarkan hasil analisis didapatkan adanya hubungan kepribadian dengn hubungan interpersonal dengan rekan kerja dengan stres kerja anggota Satlantas Polrestabes Semarang dimana menghasilkan hubungan negatif dalam kepribadian multikulturaldengan stres kerja yang semakin tinggi kepriadian multi kultural maka semakin rendah stres kerja dan akan menghasilkan kebalikannya, jika menghasilkan hubungan negatif interpersonal dengan rekan kerja dengan stres kerja dimana semakin tinggi hubungan interpersonal dengan rekan kerja maka semakin rendah stres kerja maka akan menghasilkan kebalikannya.Hal ini berarti ada hubungan antara kepribadian multikultural dan hubungan interpersonal dengan rekan kerja dengan stres kerja anggota Satlantas Polrestabes Semarang, dan secara parsial ada hubungan negatif yang sangat signifikan antara kepribadian multikultural dengan stres kerja anggota Satlantas Polrestabes Semarang, dan hubungan interpersonal dengan rekan kerja dengan stres kerja anggota Satlantas Polrestabes Semarang.Kata kunci: kepribadian multikultural, hubungan interpersonal, stres kerja)